Endogenous production of glutamine and plasma glutamine concentration in critically ill patients. (December 2020) - Smedberg, Marie; Rooyackers, Olav; Norberg, Åke; Tjäder, Inga; Wernerman, Jan
Summary: Background: Glutamine plasma concentrations outside the normal range at intensive care unit (ICU) admission are associated with unfavorable outcomes. Based on the hypothesis that hypoglutaminemia in the ICU is the result of an increased utilization of glutamine which cannot be fully met by endogenous production, extra glutamine supplementation has been advocated to ICU patients with hypoglutaminemia. However, it is still unclear whether there is a causal relation between hypo- and hyperglutaminemia and outcomes. Present guidelines advise against supplementation, although there is no evidence available for patients with hypoglutaminemia. The pathophysiology of abnormal glutamine levels and whether glutamine production or glutamine utilization is compromised is largely unknown. Therefore, the aim of this study was to elucidate the relationship between plasma glutamine levels and the endogenous glutamine production in ICU patients. Method: In this observational study, a technique using a small bolus of intravenous glutamine with an isotopic label was used to measure glutamine production. Results: There was a statistically significant correlation between de novo endogenous production of glutamine (not emanating directly from protein breakdown) and plasma glutamine concentrations in the low and normal range in circulatory stabilized ICU patients (n = 19), R 2  = 0.35 (P ≤ 0.01). Conclusion: The predictive value of a low plasma glutamine concentration at ICU admission on outcomes may thus be related to a low endogenous production, which may need to be supplemented in the best interest of this cohort of patients.